Familial Predisposition of Primary Dysmenorrhea among Senior High School Girl Students (Althea Medical Journal, 2015)
Background: Dysmenorrhea is a common female reproductive problem in women of active reproductive agewhich is characterized by menstrual pain or cramps in a women’s lower abdomen or back. Dysmenorrhea can be classified into primary and secondary. One of the associated risk factor of primary dysmenorrhoeais the family history, however the study on the family history of primary dysmenorrhea with recurrent  menstrual pain is limited. This study was conducted to identify the correlation between family history and primary dysmenorrhea in high school girls.Methods: This cross sectional study was conducted at several senior high schools in Jatinangor from Aprilâˆ’June 2013. One hundred and sixty two students were included in this study. The sample size was calculated based on the unpairedâˆ’dichotomous variable for the twoâˆ’sided formula. A self administered questionnaire was distributed to the senior high school girl students who were in their menarche age, menstrual cycle characteristics, presence or absence of dysmenorrhea, severity of pain and presence dysmenorrhea in mothers and in sisters were inquired. Data were analyzed using chi square test.Results: Overall, there were association between positive family history and primary dysmenorrhea among the students with (p
Keywords: Family history; senior high school students; primary dysmenorrhea